Electronic interactions in Ferrocene- and Ruthenocene-functionalized Tetraazamacrcocyclic Ligand complexes of FeII/III, CoII, NiII, CuII and ZnII - Comba, Peter; Linti, Gerald W. (European journal of inorganic chemistry, 2005)
The syntheses of ferrocene- and ruthenocene-functionalized tetraazamacrocyclic ligands and their corresponding transition metal complexes are described. Reaction of N,N′-bis(2-aminoethyl)-1,3-propanediamine (2,3,2-tet) with 1,1′-diformylferrocene and 1,1′-diformylruthenocene produces the ligands fcmac and rcmac in 81−85% yield. Examination of their CuII, NiII, CoII, ZnII and FeII/III complexes by IR, UV/Vis, EPR and Mössbauer spectroscopy as well as by electrochemical studies suggests electronic communication between the two metal centers of each complex. The molecular structure of [CuII(fcmac)(FBF3)]BF4, determined by X-ray structure analysis, is reported and shows that the distance between the two metals is 4.54 Å. Stability constants, determined by potentiometric titration, indicate that the copper(II) complexes are of similar stability as those with unfunctionalized tetraazamacrocyclic ligands (e.g. cyclam = 1,4,8,11-tetraazacyclotetradecane); stability constants of cobalt(II) complexes are about 2 log units smaller, those of nickel(II) and zinc(II) complexes are reduced by more than 10 log units. This selectivity is discussed on the basis of the structural studies.
Gesehen am 22.02.2018
Article was first published online on 2 December 2004